Health consequences of sex trafficking: A systematic review - Simkhada, P.; van Teijlingen, E.; Sharma, A.; Bissell, P.; Poobalan, A.; Wasti, S.P. (Journal of Manmohan Memorial Institute of Health Sciences, 2018)
Background: Sex trafficking is one of the most common forms of human trafficking globally. It is associated with health, emotional, social, moral and legal problems. The victims of sex trafficking when returned home are often ignored. This study aimed to explore the health consequences of sex trafficking among women and children.Methods: Medline EMBASE, PsycINFO and CINAHL were systematically searched, from date of inception to July 2016 using a combination of Medical Subject Headings (MeSH) and text words on health risks and consequences of sex trafficking. Electronic searches were supplemented by searching the reference lists of included papers and citation tracking. Both Qualitative and quantitative primary studies published in English and exploring health-related problems among sex trafficked women and children were included in this review. Health outcomes considered were: physical, psychological or social risks and consequences of sex trafficking among women and children. No restrictions were applied to geographical regions as sex trafficking involves victims being trafficked between different countries, and within countries. Data were extracted and study quality independently appraised by two reviewers and narrative synthesis was conducted for this review.Results: A total of fifteen articles were included covering health risks and well-being related to sex trafficking. Sexual and physical violence among victims such as rape and repetitive stress and physical injuries were common. The prevalence of STI (sexually transmitted infections) and HIV (human immunodeficiency virus) was also reported as high. Being trafficked at a young age, having been in brothels for a longer period and sexual violence and forced prostitution were linked with a higher risk for HIV infection. Physical health problems reported included headaches, fatigue, dizziness, back pain, memory problem, stomach pain, pelvic pain, gynaecological infections, weight loss, lesions or warts, unwanted pregnancies and abortions. The studies on mental health reported that depression, anxiety and post-traumatic stress disorder (PTSD) were commonly reported health consequences among sex trafficking victims.Conclusion: there is a compelling need for interventions raising awareness about sex trafficking among young girls and women most at risk of being trafficked. Most studies in this review have focussed on the physical health problems of the trafficked victims although there is also remarkable mental burden amongst those victims. Key policy makers, government officials, public health officials, health care providers, legal authorities and non-governmental organisations (NGOs) should be made aware about the health risks and consequences of trafficking. Trafficking consequences should be recognised as a health issue and all the sectors involved including regulating bodies should collaborate to fight against sex trafficking. Due to the heterogeneity of the articles, no meta-analysis could be conducted.JMMIHS.2018;4(1):130-150